Black Soldier Fly (Hermetia illucens) Larvae Meal Modulates Intestinal Morphology and Microbiota in Xuefeng Black-Bone Chickens - He, Changqing; Lei, Jiaxing; Yao, Yaling; Qu, Xiangyong; Chen, Jifa; Xie, Kailai; Wang, Xingju; Yi, Qi; Xiao, Bing; Guo, Songchang; Zou, Xiaoyan (Frontiers in Microbiology, 2021)
The addition of Hermetia illucens larvae meal (HILM) to the feed could contribute to particular antimicrobial and intestinal health in animal husbandry. This study was conducted to investigate the effects of HILM on intestinal morphology and microbial diversity in different intestinal segments of Xuefeng black-boned chickens. All of 432 birds(45‐week‐old) were randomly assigned to four equal groups with 6 replicates and 18 hens in each replicate: (A) basal diet, (B) basal diet with 1% HILM, (C) basal diet with 3% HILM, and (D) basal diet with 5% HILM, respectively. The results showed that, compared with basal diet group, HILM supplement significantly increased the ACE and Chao index in cecum (P < 0.05). Diet with 1% HILM significantly increased the villus height of duodenum (P < 0.05) and cecum microbial diversity as represented by the simpson index (P < 0.05). In particular, 1% HILM displayed markedly increase in the genus unclassified Bacteroidales (cecum, P < 0.05). Basal diet with 3% HILM markedly increased the beneficial genus Romboutsia (jejunum, P < 0.05). And PCA cluster analysis showed 3% HILM was more individual than other groups (P < 0.05). However, 5% HILM decreased the villus height and the ratio of villus height to crypt dept of jejunum, and increased beneficial bacteria such as Staphylococcus (P < 0.05), which was regarded as pathogenetic genera. In conclusion, we found that HILM improved intestinal morphology, increased microbiological diversity and species abundance. Together, dietary supplementation of 1% or 3% HILM might benefit the intestinal morphology and intestinal microbiota of Xuefeng black-boned chicken. However, the addition of 5% HILM could decrease villus height and the ratio of villus height/crypt dept of jejunum and increased pathogenetic genera. HILM was an excellent protein substitute for Xuefeng black bone chickens, which could meet the nutritional requirements under the condition of less feed. These results provide information for HILM meal as an alternative source of soybean meal in Xuefeng black bone chickens' feed.